High removal efficiency of Hg(II) and MeHg(II) from aqueous solution by coconut pith—Equilibrium, kinetic and mechanism analyses. Issue 2 (June 2016) - Saman, Norasikin; Johari, Khairiraihanna; Song, Shiow-Tien; Kong, Helen; Cheu, Siew-Chin; Mat, Hanapi
Highlights: High removal efficiency of mercury ions by CP adsorbent was obtained. Adsorption capacity of Hg(II) and MeHg(II) was 2.60 and 0.5 mmol/g, respectively. Removal performance of Hg(II) was higher than MeHg(II). High selectivity and regenerability were observed for Hg(II). Abstract: This study was conducted to investigate the high efficiency of coconut pith (CP) adsorbent in removing Hg(II) and MeHg(II) ions from aqueous solution. The CP adsorbent was characterized using a scanning electron microscope (SEM), nitrogen adsorption-desorption (NAD) analysis, determination of pH at zero point charge (pHpzc ), Fourier transform infrared (FTIR) spectroscopy and X-ray photoelectron spectroscopy (XPS). Adsorption performance of the CP adsorbent at various parameters was conducted by varying the initial pH of solution, adsorbent dosage, initial pH, temperature, and contact time. It was found that adsorption capacity, adsorption rate and enthalpy of the Hg(II) adsorption were higher compared to the MeHg(II). The adsorption capacity of Hg(II) was 2.60 mmol/g, which was five times higher than MeHg(II). The adsorption isotherm analysis showed that the Hg(II) and MeHg(II) adsorption data fitted to the Langmuir and Freundlich models, respectively. The overall mechanism of both mercury adsorptions is a combination of physical and chemical processes in which the film diffusion was the rate controlling-step. The adsorbent regenerability study results showed that the Hg(II) adsorption remained stable up to five adsorption cycles, which was better than MeHg(II). The selectivity studies reveal the potential application of the CP adsorbent for the treatment of oilfield produced water (OPW) and natural gas condensate (NGC) that are rich in mercury ions as well as other cations.